A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae) - Endruweit, Marco (Zootaxa, 2017)
Physoschistura absumbra, new species, is described from the watershed of the Salween in Cangyuan County, Yunnan Province, China. The combination of a complete lateral line, a continuous lower jaw, and the absence of a suborbital lobe distinguishes it from all other congeners. Further diagnostic characters are a long (dorsally 23–25% SL, laterally 26–28% SL) and deep head (at nape 13–14% SL), a shallow body (15–17% SL), a deep caudal peduncle (13–14% SL), 9–12 rather regular flank bars, a complete basicaudal bar, and a maximum adult size of about 44 mm SL.